Flexible regulation of active and reactive power for a fully controllable V2G wireless charger - Triviño-Cabrera, Alicia; Casaucao-Tenllado, Inmaculada; Castilla-Fernández, Miguel (IEEE, 2023)
Electric vehicles (EVs) will be an important asset in future power grids, with a dual role as flexible loads and mobile generators. To implement a complete set of vehicle-to-grid (V2G) services, the EV chargers should be adapted for bidirectional power flow considering both active and reactive power. This article proposes a simple but effective four-quadrant controller to adjust the two types of power (active and reactive) consumed or generated by the EV. Based on a theoretical analysis, it is developed the formulation to configure the power converts given a command of active and reactive power generated/consumed. As a novelty compared with previous works, any combination of the powers is possible to enable a flexible operation of the V2G wireless charger so that the vehicle can also participate in a wide range of V2G services through a wireless charger. The system is based on the series-series (SS) compensation topology, which is one of the most typical structures in wireless chargers. Experimental results at charging power up to 1 kW with a Society of Automotive Engineers (SAE) J2954 EV charger prototype demonstrate the validity of the analytical study, in each of the eight operation modes.
https://openpolicyfinder.jisc.ac.uk/id/publication/37969
Keywords: Energía eléctrica - Transporte; Vehículos eléctricos; V2G; Wireless power transfer; Control